2016
DOI: 10.1155/2016/4569108
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Adiponectin and Visfatin Concentrations in relation to Oxidative Stress Markers in Neonates Exposed and Nonexposed In Utero to Tobacco Smoke

Abstract: Aims. Maternal smoking is considered as a source of oxidative stress, which has been implicated to disrupted adipokines expression in adipose tissue. We examined the relationship between selected adipokines and markers of oxidative stress/antioxidant defence in the umbilical cord of neonates exposed and nonexposed in utero to tobacco smoke. Methods. Subjects including 85 healthy neonates (born to 41 smokers and 44 nonsmokers) were tested for adiponectin, visfatin, oxidized low density lipoprotein (ox-LDL), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In the presented study, we observed that the intensification of oxidative processes dependent on tobacco smoke significantly influenced glutathione homeostasis. Moreover, our research confirmed the adverse effect of smoking on the oxidant status of both mothers and children [13,19,20]. As mentioned above, as a thiol compound, glutathione plays an extremely important role in enzymatic and non-enzymatic reactions for protecting cells against oxidative stress damage induced by cigarette smoking [23].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the presented study, we observed that the intensification of oxidative processes dependent on tobacco smoke significantly influenced glutathione homeostasis. Moreover, our research confirmed the adverse effect of smoking on the oxidant status of both mothers and children [13,19,20]. As mentioned above, as a thiol compound, glutathione plays an extremely important role in enzymatic and non-enzymatic reactions for protecting cells against oxidative stress damage induced by cigarette smoking [23].…”
Section: Discussionsupporting
confidence: 81%
“…All newborns, regardless of prenatal tobacco smoke exposure, are particularly susceptible to oxygen damage due to the conditions generating increased production of free radicals with incomplete maturity of antioxidant systems and the high energy demand of rapidly growing tissues [ 16 ]. Elevated levels of oxidative stress markers in the cord blood of infants born to mothers who smoked actively during pregnancy were also documented, suggesting that exposure to tobacco smoke in utero intensifies oxidative stress in newborns [ 13 ]. Here, we have found a close relationship between TOC concentration, cotinine, and glutathione level in the cord blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased visfatin along with resistin was associated with increased diabetes and cardiovascular risk in obese patients[ 37 ]. In another study, higher visfatin and TOS and lower TAS levels were observed in infants born to mothers who smoked[ 38 ]. Patients with psoriasis were evaluated for the same relationship.…”
Section: Discussionmentioning
confidence: 99%
“…It is described that SHS leads to metabolic syndrome in adolescents [106] and children, especially in combination with low intake of vitamin E or omega-3 polyunsaturated fatty acids [107]. Neonates exposed to PTS were shown to have lower levels of adiponectin and higher levels of visfatin, indicating a less beneficial OS profile compared to non-exposed new-borns [108]. In an urban study, adolescents exposed to SHS showed an increase in urinary 15-F 2t -isoprostane, a specific product of lipid peroxidation and biomarker for OS level [109].…”
Section: Oxidative Stressmentioning
confidence: 99%